2020
DOI: 10.3389/fcell.2020.00392
|View full text |Cite
|
Sign up to set email alerts
|

High Cancer Susceptibility Candidate 8 Expression Is Associated With Poor Prognosis of Pancreatic Adenocarcinoma: Validated Analysis Based on Four Cancer Databases

Abstract: The aim of this study was to explore the association between the expression of a long non-coding RNA (lncRNA), cancer susceptibility candidate 8 (CASC8), and pancreatic adenocarcinoma (PAAD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Among the seven lncRNAs used to construct the signature, AC092171.5 has previously been reported as an immune-and m6A-related lncRNA in pancreatic cancer and is significantly associated with patient prognosis (Wei et al, 2019;Cao et al, 2022). CASC8 has been suggested as a marker to predict the prognosis of PAAD and as a potential target for treatment (Wang et al, 2020;Ping et al, 2022), which is consistent with our findings. AC090114.2 was reported to be a pyroptosis-related lncRNA and was associated with PAAD prognosis and tumor immune microenvironment Frontiers in Genetics frontiersin.org (Zhao et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Among the seven lncRNAs used to construct the signature, AC092171.5 has previously been reported as an immune-and m6A-related lncRNA in pancreatic cancer and is significantly associated with patient prognosis (Wei et al, 2019;Cao et al, 2022). CASC8 has been suggested as a marker to predict the prognosis of PAAD and as a potential target for treatment (Wang et al, 2020;Ping et al, 2022), which is consistent with our findings. AC090114.2 was reported to be a pyroptosis-related lncRNA and was associated with PAAD prognosis and tumor immune microenvironment Frontiers in Genetics frontiersin.org (Zhao et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…The competing endogenous RNA mechanism has been constructed using the TCGA-PAAD dataset by Wenjuan Zhu et al, who then identified CASC8 as a potential therapeutic target for pancreatic cancer 46 . This has also been confirmed by Yingyi Wang et al 47 . Afterward, the model was systematically validated for its reliable applicability and clinical predictive accuracy in terms of PCA, survival analysis of clinical subgroups and different cohorts, and independent prognostic analysis.…”
Section: Discussionsupporting
confidence: 77%
“…CASC8 is located on chromosome 8q24, and its specific upregulation in pancreatic adenocarcinoma might indicate poor prognosis 45 . These findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%